Springer Handbook of Odor - Buettner, Andrea (Springer Handbooks, 2017)
The Springer Handbook of Odor is the definitive guide to all aspects related to the study of smell and their impact on human life. For the first time, this handbook aligns the senso-chemo-analytical characterization of everyday smells encountered by mankind, with the elucidation of perceptual, hedonic, behavioral and physiological responses of humans to such odors. From birth onwards we learn to interact with our environment using our sense of smell. Moreover, evolutionary processes have engendered a multi-faceted communication that is supported - even dominated - by olfaction. This compilation examines the responses of humans to odors at different stages of life, thereby building a foundation for a widely overseen area of research with broader ramifications for human life. The expert international authors and editor align aspects, concepts, methodologies and perspectives from a broad range of different disciplines related to the science of smell. These include chemistry, physiology, psychology, material sciences, technology but also disciplines related to linguistics, culture, art and design. This handbook, edited by an internationally renowned aroma scientist with the support of an outstanding team of over 60 authors, is an authoritative reference for researchers in the field of odors both in academia and in industry and is also a useful reference for newcomers to the area.- Resumé vydavatel